Nerve transfer surgery in cervical spinal cord injury: a qualitative study exploring surgical and caregiver participant experiences. Issue 11 (22nd May 2021) - Fox, Ida; Hoben, Gwendolyn; Komaie, Goldie; Novak, Christine; Hamm, Rebecca; Kahn, Lorna; Whitehead, Meredith; Juknis, Neringa; Ruvinskaya, Rimma; Mackinnon, Susan; James, Aimee
Abstract: Purpose: To investigate perceptions of surgical participants and their caregivers regarding novel nerve transfer surgery to restore upper extremity function in cervical level spinal cord injury. Materials and Methods: A qualitative study design was used. A multidisciplinary team developed semi-structured interview guides. Interviews were recorded, transcribed and analyzed using basic text analysis. Results: Participants had limited information about procedures to improve function after spinal cord injury. When discussing their choice to undergo nerve (as compared to traditional tendon) transfer surgery, they describe a desire to avoid post-operative immobilization. Barriers included the pre-operative testing, cost and inconvenience of travel for surgery, and understanding complex health information related to the procedure. While expectations matched descriptions of outcomes among participants and were generally positive, caregivers expressed disappointment. The long time interval for gains in function to be realized and relatively incremental gains achieved were frustrating to all. Conclusions: People with cervical spinal cord injury and their caregivers need more information about options to restore function and about realistic range of improvements with treatment. Further work to mitigate barriers and develop health information materials around nerve transfer surgery may improve medical decision making around and appropriate use of this newer treatment option. IMPLICATIONS FOR REHABILITATION: Nerve transfer surgery is a novel and acceptable means of improving upper extremity function in the setting of cervical spinal cord injury. People with cervical spinal cord injury and their caregivers need information about options to restore hand and arm function and mitigation of barriers around these treatment options.